Conservative treatment in early stage endometrial cancer: a review - Trojano, Giuseppe; Olivieri, Claudiana; Tinelli, Raffaele; Damiani, Gianluca Raffaello; Pellegrino, Antonio; Cicinelli, Ettore (Acta Biomedica Atenei Parmensis, 2019)
Endometrial Cancer (EC) is the commonest gynecological cancer and its incidence is increasing. The diagnosis of endometrial carcinoma in young women of childbearing age is rare. Indeed, only 4% of patients with endometrial carcinoma are